A Three-Layer Metadata Model for the Digital Inventory of Kasab Aceh - Hardisal; M Arynal Ihsan (Jurnal Inotera, 2025)
Kasab Aceh—raised gold-thread embroidery worked on velvet—embodies aesthetic, symbolic, and social meaning across Aceh’s regions. Yet its diverse forms and motifs remain unevenly documented in digital repositories, limiting preservation and scholarly reuse. This article presents a concise yet comprehensive, three-layer metadata model—descriptive, administrative, and structural—for the digital inventory of Kasab Aceh. The design adapts Dublin Core for interoperable description and aligns with CIDOC CRM to support event-centric semantics and future publication as Linked Open Data. We delineate core entities (Product, Motif, Artisan, Photo, Session, Region, Registration), cardinalities (e.g., Product–Motif M:N; Photo–Product N:1), normalization policies (centimeters/grams for measurements; free-text materials and colors), and session-based provenance. Results include an Entity–Relationship schema, illustrated instances from South Aceh fieldwork, and a validation regimen using SHACL constraints. We discuss practical trade-offs between field flexibility and data consistency, demonstrate how structural links to image-derivative files (mask/overlay/SVG/JSON) enable reproducible visual analytics, and outline pathways for semantic migration and public access. The model offers a durable foundation for culturally faithful curation and cross-disciplinary research.